FACIES AND STRUCTURAL CONTRASTS ACROSS BONNE BAY CROSS-STRIKE DISCONTINUITY, WESTERN NEWFOUNDLAND - Cawood, Peter Anthony; BOTSFORD, J W (1991)
The Bonne Bay cross-strike discontinuity of western Newfoundland corresponds with major along-strike changes in depositional facies and structural styles of rock units overlying Grenville basement. Facies associations in time-equivalent Lower Ordovician rock units of the Humber Arm Allochthon change abruptly in character at Bonne Bay. Redeposited shelf carbonates are absent from the allochthonous Upper Tremadocian to Arenig sediments south of the bay but present in time equivalent sediments to the north. The influx of synorogenic foreland-basin flysch commences at least one graptolite zone earlier to the south of the cross-strike discontinuity than to the north. South of Bonne Bay, the complete structural succession of the Humber Arm Allochthon is preserved, whereas to the north only the lower structural slices of the allochthon are present. The cross-strike discontinuity corresponds with the southern limit of the Acadian uplift of the Grenville Long Range Inlier and also marks a reversal in Acadian structural vergence from west-directed folds and thrust in the north to east-directed folds and thrusts in the south. The Bonne Bay cross-strike discontinuity is inferred to represent a transfer fault formed during continental rifting at the inception of the Appalachian cycle that was reactivated during the subsequent history of the orogen. Additional cross-strike discontinuities, inferred on the basis of along-strike changes in the style of Taconian and Acadian orogenesis, probably occur near the southern boundary of the Humber Arm Allochthon and at the northern and southern boundaries of the Hare Bay Allochthon. These zones, like the Bonne Bay structure, appear to mark the boundaries of small-scale (second-order) promontories and reentrants in the Humber Zone margin, which controlled allochthon emplacement and subsequent Acadian orogenic deformation.